Hematological spectrum in patients with alcoholic liver cirrhosis: a model of end-stage liver disease score based approach - Jain, Deepak; Aggarwal, H. K.; Rao, Avinash; Dahiya, Shaveta; Singla, Suhas (International Journal of Advances in Medicine, 2017)
Background: Patients with alcoholic liver cirrhosis have anaemia, leucocytosis as well as leukopenia and thrombocytopenia in various proportions, which are, to a greater extent, determine mortality and morbidity among them. There is a growing need of a scale to determine the stages at which these hematological parameters could be corrected so as to decrease their adverse impacts on the patients’ lives. The model of end-stage liver disease (MELD) score is built to predict survival in cirrhotic patients undergoing transplantation and to assign priority for liver transplantation. To simplify the task of early identification and management of patients with deranged blood indices, we studied the relationship between various hematological parameters and MELD score. Methods: This was a prospective observational study in which spectrum of various hematological indices and complications of alcoholic liver disease were observed in 88 patients with stigmata of chronic liver failure on clinical examination substantiated by histopathological evidence and imaging. Hematological parameters including anaemia, leukocyte count and platelet count were assessed in the subjects and were categorized under the different groups of MELD score. The relationship of these variables with MELD score was studied and statistical analysis was done. Results: We observed a progressive fall in hemoglobin levels with the increase in MELD score. All the patients in group 1 had normal leukocyte count. Leukocytosis predominated in MELD group 2 and 3 patients. In group 4, leukopenia was more prevalent. All the patients in group 5 had leukopenia. Group 1 and 2 patients did not have thrombocytopenia. Thrombocytopenia started occurring in MELD group 3 patients, while involving all the patients of group 4 and 5. Conclusions: The statistically significant association between the variables and the groups shows that MELD score grouping system could be an important tool in the assessment of these patients. This association strongly depicts that the clinicians could effectively apply the classification in predicting the hematological complications in these patients and take precautions early in preventing the further progression of the disease thus decreasing the mortality in these patients.